The Miraculous Virgin: Journey from Novella to Shooting Script - Michalovič Michal (Slovenské divadlo)
Dominik Tatarka’s novella The Miraculous Virgin was first published in 1944. Twenty years later a second edition (revised by the author) was published and at approximately the same time Tatarka wrote a literary script for an intended film based on his novella. Director Štefan Uher (who had previously directed three feature films – Class Nine A, The Sun in a Net and The Organ) undertook the film adaptation. He wrote the shooting script based on Tatarka’s literary script and in 1966 he directed the movie The Miraculous Virgin. In the present study the author analyses the evolution of the text from one version to another. Tatarka’s modifications to the text and Uher’s subsequent changes are being analysed. The readers – and future audience of the film – had at their disposal four literary versions of The Miraculous Virgin: two editions of the novella, a film treatment by Tatarka (published in two issues of the Slovenské pohľady magazine in 1964) and a so-called literary script (published in 1966). Therefore we can talk about a complex consisting of various components and we can analyse in detail the relationship between them.